Axonal motor protein KIF5A and associated cargo deficits in multiple sclerosis lesional and normal‐appearing white matter. (1st April 2016) - Hares, K.; Redondo, J.; Kemp, K.; Rice, C.; Scolding, N.; Wilkins, A.
Abstract : Aims: Understanding the causes of axonal pathology remains a key goal in the pursuit of new therapies to target disease progression in multiple sclerosis (MS). Anterograde axonal transport of many proteins vital for axonal viability is mediated by the motor protein KIF5A, which has been linked to several neurological diseases. This study aimed to investigate the expression of KIF5A protein and its associated cargoes: amyloid precursor protein (APP) and neurofilament (NF) in post mortem MS and control white matter (WM) and to determine if KIF5A expression is influenced by the presence of MS risk single nucleotide polymorphisms (SNPs) identified in the region of the KIF5A gene. Methods: Using immunoblotting assays we analysed the expression of KIF5A, APP and NF phospho‐isoforms in 23 MS cases and 12 controls. Results: We found a significant reduction in KIF5A and associated cargoes in MS WM and an inverse correlation between KIF5A and APP/NF protein levels. Furthermore, homozygous carriers of MS risk gene SNPs show significantly lower levels of KIF5A protein compared to MS patients with no copies of the risk SNPs. Conclusions: We conclude that reduced expression of axonal motor KIF5A may have important implications in determining axonal transport deficits and ongoing neurodegeneration in MS. Abstract : Investigation of KIF5A, a mediator of anterograde protein transport, in multiple sclerosis indicates that axonal transport deficits may contribute to neuronal degeneration and that this may be influenced by genotype.